Design of One-Dimensional Linear Phase Digital IIR Filters Using Orthogonal Polynomials. (16th October 2012) - Kumar, Vinay; Bhooshan, Sunil
Abstract : In the present paper, we discuss a method to design a linear phase 1-dimensional Infinite Impulse Response (IIR) filter using orthogonal polynomials. The filter is designed using a set of object functions. These object functions are realized using a set of orthogonal polynomials. The method includes placement of zeros and poles in such a way that the amplitude characteristics are not changed while we change the phase characteristics of the resulting IIR filter.